Identification and Allelic Variants Associated With Cold Tolerance of PmPIAS in Pinctada fucata martensii - Lai, Zhuoxin; Adzigbli, Linda; Chen, Qingyue; Hao, Ruijuan; Liao, Yongshan; Deng, Yuewen; Wang, Qingheng (Frontiers in Physiology, 2021)
The protein inhibitor of activated STAT (PIAS) functions in diverse aspects, including immune response, cell apoptosis, cell diﬀerentiation and proliferation. In the present study, the PIAS in the pearl oyster Pinctada fucata martensii was characterized. The sequence features of PmPIAS were similar to that of other PIAS sequences with PIAS typical domains, including SAP, Pro-Ile-AsnIle-Thr (PINIT), RLD domain and AD, S/T rich region. Homologous analysis showed that PmPIAS protein sequence showed the conserve primary structure compared with other species. Ribbon representation of PIAS protein sequences also showed conserved structure among species, and the PINIT domain and RLD domain showed the conserved structure compared with the sequence of Homo sapiens. Expression pattern of PmPIAS in different tissues showed significant highly expression in the gonad. PmPIAS also exhibited a significantly higher expression in the 1D and 2D after cold tolerance stress (17℃) and showed its potential in the cold tolerance. The SNP analysis of exon region of PmPIAS obtained 18 SNPs and among them, 11 SNP represented significant among different genotypes and alleles between cold tolerance selection line and base stock which showed their potential in the breeding for cold tolerance traits.